2015
DOI: 10.15376/biores.10.4.7455-7465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Reinforced Poplar Laminated Veneer Lumber

Abstract: Three types of reinforcement materials, a carbon fiber-reinforced polymer (CFRP) sheet, a glass fiber-reinforced polymer (GFRP) mesh, and a composite of the CFRP sheet and GFRP mesh, were used to reinforce poplar laminated veneer lumber (LVL), and the multi-step hotpressing method was also applied. The mechanical properties, i.e., modulus of rupture (MOR), modulus of elasticity (MOE), and horizontal shear strength (HSS), of the reinforced LVL were investigated, as well as the effects of lay-up location of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…The thickness swelling was slightly higher, but the water absorption was lower than usually found in the literature for LVL [15]. Probably the main reason behind this behavior is the level of pressure applied.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The thickness swelling was slightly higher, but the water absorption was lower than usually found in the literature for LVL [15]. Probably the main reason behind this behavior is the level of pressure applied.…”
Section: Resultsmentioning
confidence: 65%
“…Wang et al [14] found f m ranged from 79.9 to 90.5 N/mm 2 whereas the E M ranged from 8362–9185 N/mm 2 for non-reinforced poplar PF resin-bonded LVL. Recently, Bal [15] also evaluated the properties of PF-bonded poplar LVL and found 66.1 N/mm 2 for f m and 5433 N/mm 2 for E M . The values presented here were also between the range presented by the Forest Products Laboratory [16] for E M (4900–12,500 N/mm 2 ) and f m (33.8–88.2 N/mm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bal [27] found MOR ranged from 79.9 to 90.5 N/mm 2 whereas the MOE ranged from 8362-9185 N/mm 2 for non-reinforced poplar PF resin-bonded LVL. Recently, Wang et al [28] also evaluated the properties of PF-bonded poplar LVL and found 66.1 N/mm 2 for MOR and 5433 N/mm 2 for MOE. The values presented here are also between the range presented by the Forest Products Laboratory [29] for MOE (4900-12500 N/mm 2 ) and MOR (33.8-88.2 N/mm 2 ) for the experimental cases T5, T6 and T7, with T6 performing in general better that the other two.…”
Section: Muf Resinmentioning
confidence: 99%
“…Furthermore, previous works have demonstrated the importance of the quality of the wood used in laminated lumber under bending stresses [15]. The use of carbon and basalt fiber reinforced polymers (CFRP and BFRP, respectively) has been studied in sawn wood and technological products such as glulam and LVL elements, demonstrating the improvement of mechanical properties under different reinforcement configurations [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%